Melanoma malignum of nasal cavity and paranasal sinuses - Nazim-Zygadło, Elżbieta; Kochanowicz, Jan (Contemporary Oncology/Współczesna Onkologia, 2001)
The paper presents a case of a 67 year old patient with a melanoma malignum of the nasal cavity and paranasal sinuses. Attention has been drawn to the rare occurrence of this neoplasma in this area as well as its treatment.